The answer to #2?? I already have the graph but I still need the answer
1 answer:
If we have
y = 6x + 1 and x - y = 11, we can take advantage of y - y = 0 as follows:
Subtract x from both sides of the 2nd equation:
-y = 11 - x
Now combine
y = 6x + 1
-y = 11 - x
--------------
0 = 5x + 12. Solving for x, x = -12/5. Using the equation above, find y:
-y = 11 - x
= 11 - (-12/5)
= 55/5 + 12/5 = 67/5
Then the solution is (-12.5, 67/5).
You might be interested in
I believe it is the second one
B is the correct answer I think
Answer:
13.5
Step-by-step explanation:
Answer:2
Step-by-step explanation:
Answer:
8
Step-by-step explanation:
so my school uses the method called kcf (keep change flip)
keep the 4
change the division sign to a multiplication sign
flip 1/2 to 2/1
4x2=8